Foreword (Historia, 2021)
Johan Bergh turns sixty in 2006. It is also his twentieth year as Head of the History Department at the University of Pretoria and as Chair of the Historical Association of South Africa (HASA). In addition, this year marks the fiftieth anniversary of the founding of the Historical Association (HASA) in 1956. For this special occasion of "round numbers" culminating in one career, a call was sent out to colleagues of Johan Bergh, as well as to research associates of his Department, and also to .